Knowledge, Attitude and Practice in Management of Atypical Odontalgia among Dentists - Acharya, Nisha; Karmacharya, Anu; Acharya, Sayana; Paudel, Durga; Murakami, Satoshi; Abiko, Yoshihiro (Journal of Institute of Medicine Nepal, 2025)
Introduction Atypical odontalgia (AO) is one of the representatives of medically unexplained oral symptoms (MUOS) and is characterized by persistent orofacial pain in absence of any significant clinical or radiographic findings. These conditions are often associated with neuropathic, vascular or psychiatric disorders. It is frequently misdiagnosed leading unnecessary treatments. This study assesses knowledge, attitude, and practices regarding AO among dentists. Methods In this descriptive cross-sectional study, set of 20 questions was developed and tested for face and content validity. Pretesting was done on 10% of the sample (N=181), and necessary modifications were made. The final questionnaire was distributed via Google Forms, and 181 responses were collected. Data were analyzed using SPSS v20. Results Among 181 study participants, 176 (97.2%) actively practiced dentistry to date, and 129 (71.3%) encountered patients with atypical odontalgia. More than half of them, 104 (57.5%) used the term atypical odontalgia, followed by other terminologies like psychogenic pain (23, 12.7%) and chronic idiopathic pain (26, 14.4%). Most of them (93, 51.4%) thought that atypical odontalgia may be of neuropathic, psychological, or vascular in origin. At least once in every six months, or once during their practice, atypical odontalgia was encountered by 35 dentists (19.3%). Out of 181 dentists, 53 (29.3%) have confidence in the management of AO. However, most of them referred to an oral medicine specialist. Conclusion Although atypical odontalgia was commonly encountered in dental practices, notable gaps in attitude, knowledge and management or treatment practices was seen.